2008
DOI: 10.1016/j.freeradbiomed.2007.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Silica binding and toxicity in alveolar macrophages

Abstract: Inhalation of the crystalline form of silica is associated with a variety of pathologies from acute lung inflammation to silicosis, in addition to autoimmune disorders and cancer. Basic science researchers looking at the mechanisms involved with the earliest initiators of disease are focused on how the alveolar macrophage (AM) interacts with the inhaled silica particle and the consequences of silicainduced toxicity on the cellular level. Based on experimental results, several rationales have been developed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
249
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(256 citation statements)
references
References 116 publications
5
249
0
2
Order By: Relevance
“…As confocal microscope fi ndings showed that MNP@SiO 2 could enter the cell after treatment, irrespective of size, it may be owing to early cellular entry of MNP@SiO 2 . Base on recent reports that toxicity of silica nanoparticles was mediated through oxidant generation (Akhtar et al, 2010), and treatment of silica nanoparticles induced infl ammation (Hamilton et al, 2008) and enhanced infl ammatory cytokines (Nishimori et al, 2009), they could induce cellular toxicity even in larger size as well as small size.…”
Section: Discussionmentioning
confidence: 99%
“…As confocal microscope fi ndings showed that MNP@SiO 2 could enter the cell after treatment, irrespective of size, it may be owing to early cellular entry of MNP@SiO 2 . Base on recent reports that toxicity of silica nanoparticles was mediated through oxidant generation (Akhtar et al, 2010), and treatment of silica nanoparticles induced infl ammation (Hamilton et al, 2008) and enhanced infl ammatory cytokines (Nishimori et al, 2009), they could induce cellular toxicity even in larger size as well as small size.…”
Section: Discussionmentioning
confidence: 99%
“…DPPC, the major component of lung surfactant, dispersed in physiological saline, has been used as simple model of lung surfactant in particle toxicity studies [Foucaud et al, 2007;Porter et al, 2008;Sager et al, 2007;Wallace et al, 1992;Wallace et al, 2007b]. In the case of silica toxicity, DPPC has been used as protective agent, inhibiting toxicity by particle coating [Hamilton et al, 2008;Patzold et al, 1993;Schimmelpfeng et al, 1992;Wallace et al, 1992]. However, it did not have a protective effect on chrysotile asbestos toxicity [Schimmelpfeng et al, 1992].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DPPC can affect particle toxicity by altering their surface chemistry and ultimately changing their toxicity [Buford et al, 2007;Hamilton et al, 2008;Wallace et al, 2007a;Wallace et al, 2007b]. Any potential contribution to the observed effects can be established by investigations which are currently underway.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that treatment of macrophages with silica is cytotoxic (19). To determine whether silica-induced cytotoxicity was associated with Nalp3, we assessed the degree of cell death in WT and Nalp3-deficient macrophages after silica treatment.…”
Section: Silica and Asbestos Induce Il-1␤ Secretion In A Nalp3-dependentmentioning
confidence: 99%